2018
DOI: 10.1007/s11130-018-0703-0
|View full text |Cite
|
Sign up to set email alerts
|

Amantagula Fruit (Carissa macrocarpa (Eckl.) A.DC.): Nutritional and Phytochemical Characterization

Abstract: Fruits are one of the most promising food matrices and they have been explored in the discovery of new natural and safer bioactive compounds. Carissa macrocarpa (Eckl.) A. DC. fruits are widely consumed in African countries for the preparation of traditional foodstuff, but also for their beneficially health effects. Thus, as the authors' best knowledge there are no studies on the chemical and bioactive characterization of these fruits. Therefore, fruits of C. macrocarpa from Tunisia were chemically characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…Crude fiber content measures the indigestible components such as cellulose and lignin contained in the fruits [29]. The ash content was found to be (0.52 %) which is similar to the earlier study reported by Souilem et al 2019 [31] concerning the fruits of Carissa macrocarpa that was reported to contain 0.5 % ash content. The ash content measures the amount of minerals available or contained in a fruit.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Crude fiber content measures the indigestible components such as cellulose and lignin contained in the fruits [29]. The ash content was found to be (0.52 %) which is similar to the earlier study reported by Souilem et al 2019 [31] concerning the fruits of Carissa macrocarpa that was reported to contain 0.5 % ash content. The ash content measures the amount of minerals available or contained in a fruit.…”
Section: Resultssupporting
confidence: 82%
“…The ash content measures the amount of minerals available or contained in a fruit. The carbohydrate content (10.49 %) is lower than that of the Carissa macrocarpa (16.40 %) and Carissa spinarum (18.66 %) reported by Souilem et al (2019) [31] and Chauhan et al (2015) [32] respectively, meanwhile, the sugar content (17.50 g) was higher than that of Carissa macrocarpa [31]. The total solid content is 28.04 %, fat (0.3 %) which is lower than that of Carissa spinarum (1.30 %) reported by Chauhan et al 2015 [32].…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…The plant also cultivated in Egypt El-Orman garden and grows as a shrub (3-4 m height). It is a spiny, evergreen latex containing shrub with yellowish white flowers and delicious red fruits [5,6]. In traditional medicine Carissa species used in the treatment of diarrhea and venereal diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is a spiny, evergreen latex containing shrub with yellowish white flowers and delicious red fruits [5,6]. In traditional medicine Carissa species used in the treatment of diarrhea and venereal diseases [5]. A large number of diverse chemical constituents having important economic and biological values were detected in Carissa species such as; sterols & triterpenes [7,8], anthraquinones, saponins, tannins, [9,10], cardiac glycosides [11,12] alkaloids [13].…”
Section: Introductionmentioning
confidence: 99%